Learning from expert or own practice: reflectively editing video cases for professional development. Issue 2 (4th March 2023) - Sancar, Raziye; Atal, Deniz
ABSTRACT: This research aimed to investigate how the video editing process professionally affected preservice teachers' reflection levels and whether it differed by the type of in-class teaching experiences (their own and expert teacher experiences). The editing procedure of video cases means selecting and combining parts from an entire recorded in-class teaching experience and adding reflective thinking on actions. Seven participants took part in the research process during a semester, with three-cycle of the video case editing procedures being applied separately to two different research groups. Both inductive and deductive content analysis procedures were applied in a total of 21 video cases edited by PTs. By editing in-class teaching experiences, PTs could deeply analyse the events and transform their reflections on the contextual features. The process facilitated PTs' professional development by identifying, noticing, and reflecting on in-class teaching experiences. PTs learned to analyse their experiences by using different types of perspectives. PTs could deeply analyse the events and transform their reflections on the contextual features. Contrary to the difficulties for PTs' reflection-in-action, the process of editing in-class teaching experiences expanded their reflection-on-action opportunities.